Ground plane impact on the threshold voltage of relaxed ge pfinfets - Goncalves, G. V.; Oliveira, A. V.; Agopian, P. G.D. [UNESP]; Martino, J. A.; Witters, L.; Mitard, J.; Collaert, N.; Claeys, C.; Simoen, E. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper the Ground Plane (GP) influence on the threshold voltage of Ge pFinFET devices is investigated. In order to explain the experimental threshold voltage variation with fin width, TCAD simulations have been utilized. There are two main process parameters varied in the numerical simulations: a different ground plane peak doping concentration and the distance between the bottom part of the fin and the ground plane. The threshold voltage variation reaches up to 80 mV from the narrowest device to the widest one, for the studied ground plane doping concentration range. Additionally, the slope of the curve of the threshold voltage as a function of channel width varies from 250μV/nm till around 700 μV/nm.
Keywords: FinFET; Germanium; P-type; STI last